U.S. UNIVERSITY WEBSITES AS SPECIFIC MULTIMODAL TEXTS - Svitlana V. Fedorenko; Kateryna B. Sheremeta (Вісник університету ім. А. Нобеля. Серія Філологічні науки, 2023)
The aim of the article was to study the specifics of the interfaces of the U.S. university websites as multimodal heterogeneous texts that synthesize elements of educational, scientific and advertising discourses. The overall objectives to achieve the established goal were as follows: to identify and distinguish the types of multimodal means on the U.S. university website, which contribute to its genre mixing and genre embedding; to establish the nature of the interaction of verbal, non-verbal and para-verbal components of the U.S. university websites, and to determine their pragmatic features. The methodological basis of the research was a complex of the following methods: analysis (to study multimodal components of the university website as a specific multimodal text), synthesis (to identify the features of the integration of multimodal means of the websites of American universities), observation (for the selection of fragments with verbal means that actualize the visual content and the selection of visual fragments to actualize the verbal content), the method of discourse analysis (to highlight specific fragments of websites that arouse the interest of the authors of this articleб and have a meaningful content), structural method (to analyze the university website as a whole structure, which is provided by separate means of cohesion), functional method (to clarify the pragmatic potential of multimodal elements of the university website, which are means of communication between the university and the reader of its website). It also employed the system functional (drawing on the provisions of linguistic metafunctions, and focusing on the categories of the grammar of visual design) and the socio-semiotic (grounding on the interrelationship of modes, their compatibility and social needs for which they serve, making meanings) approaches. The chosen methodology made it possible to conduct a study of the multimodality of the websites of the U.S. universities, realized as a symbiosis of verbal, non-verbal and paraverbal resources. The multimedia corpus of the research consists of the websites of five American universities (Massachusetts Institute of Technology, Harvard University, University of Pennsylvania, Yale University and Рrinceton University). The main conclusion that can be drawn is that the complex discursive nature of the websites under study is determined by the features inherent in advertising (the benefits of services to influence the choice of the recipient), educational (the talk about the educational process and educational services) and scientific (information of a scientific nature is provided) discourses. All universities under study employ semiotic landscapes at their disposal to portray attractive brands on their websites. Being the most important way to ensure fast and effective communication of educational institutions with their target audience, the discourse of university websites has a pronounced pragmatic orientation. The purpose of the analyzed type of heterogeneous discourse is to create an image of an “ideal” educational institution, attract potential students, researchers, sponsors, and disseminate the latest achievements in the field of science and education. The concept of multimodality of the websites of the analyzed U.S. universities as specific multimodal texts is manifested in visual content through a number of paragraphemic and infographic elements, the synthesis of which is due to the combination of language tools, visual content and web technologies of modern website construction. The most common visual content exploited on the U.S. university websites embraces: unique photographs and “color” mode (photos of the university and its students, classrooms, laboratories, events, etc.), which helps to clearly illustrate the educational services offered, and give the desired emotional mood; infographics and data visualization, which is an effective way to combine text, pictures and design to present complex information (infographics do not always completely replace the text, more often it is its addition or retelling); video interviews with students, graduates, videos about studying at a university are one of the means to convince potential students to make an admission decision. Using video is a fairly popular form of visual content. With the help of video, the universities can not only diversify the content of their websites, but also satisfy the needs of those users who prefer visual content. Placing various videos on website pages allows solving the problems of reinforcing textual content, strengthening the arguments “for” admission and attracting applicants to university educational programs. In such a way, on the basis of the interaction of different discourses (advertising, educational and scientific) and various semiotic systems, a single visual-structural and functionally complete image of an attractive and popular university is achieved among readers of its website.